Maybe, Maybe ... PhD Baby? - Chesser, Stephanie (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
Although academic publications over the past several decades have steadily reportedthe perspectives of female academics related to the topic of motherhood, less attentionhas been paid to the specific factors that influence when and why PhD students havechildren. With greater numbers of doctoral graduates entering postdoctoral studies(many at an age when the average Canadian is contemplating having their firstchild), it seems necessary that student voices be added to discussions concerning familyin the academy. This personal narrative essay intends to explore some of the factorsthat might impact family planning for doctoral students. Utilizing journal entrieswritten by the author during her undergraduate and graduate training, issues suchas the timing of pregnancy in the life course, pronatalism, the presumed existence ofa woman’s biological clock, and unintended pregnancy will be critically examined.